2000
DOI: 10.1016/s0375-9474(00)00141-x
|View full text |Cite
|
Sign up to set email alerts
|

Quark delocalization, color screening model and nucleon–baryon scattering

Abstract: We apply the quark delocalization and color screening model to nucleonbaryon scattering. A semi-quantitative fit to N-N, N-Λ and N-Σ phase shifts and scattering cross sections is obtained without invoking meson exchange. Quarks delocalize reasonably in all of the different flavor channels to induce effective nucleon-baryon interactions with both a repulsive core and with an intermediate range attraction in the cases expected. 25.80.-e 25.10.+s 13.75.-n 25.40.-h Typeset using REVT E X

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Noticing the similarity between the force of hadrons and that of atoms, quarks confined in one nucleon are speculated to delocalize into another nucleon [369], which leads to the screened confinement potential between quarks belonging to different nucleons. Along this line, there were many investigations on the various aspects of hadron properties [370,371,372,373,374]. It was shown that the modified confinement potential gives an equivalent description for the contribution from the hidden-color channels [375].…”
Section: Chiral Quark Modelmentioning
confidence: 99%
“…Noticing the similarity between the force of hadrons and that of atoms, quarks confined in one nucleon are speculated to delocalize into another nucleon [369], which leads to the screened confinement potential between quarks belonging to different nucleons. Along this line, there were many investigations on the various aspects of hadron properties [370,371,372,373,374]. It was shown that the modified confinement potential gives an equivalent description for the contribution from the hidden-color channels [375].…”
Section: Chiral Quark Modelmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31]. Here, we just present the salient features of the model.…”
Section: The Quark Delocalization Color Screening Model (Qdcsm)mentioning
confidence: 99%
“…The delocalization parameter is determined by the dynamics of the interacting quark system, and it thus allows the quark system to choose the most favorable configuration through its own dynamics in a larger Hilbert space. The model gives a good description of nucleon-nucleon and hyperonnucleon interactions and the properties of the deuteron [24][25][26][27][28]. It is also employed to calculated the baryon-baryon scattering phase shifts and the dibaryon candidates in the framework of the resonating group method (RGM) [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown [3] that there are three types of baryon-baryon bound states. The states of the first type are called deuteron-like states.…”
Section: Introductionmentioning
confidence: 99%
“…There were number of theoretical predictions by using various models [3], the quark cluster model [10], the quark-delocation model [11,12], the chiral SU(3) quark model [13], the flavor SU(3) skyrmion model [14]. Lomon predicted a deuteron-like dibaryon resonance using R-matrix theory [15].…”
Section: Introductionmentioning
confidence: 99%